Synthesis of Gold Nanorices on ITO Substrate Using Silver Seed-Mediated Growth Method - Nafisah, Suratun; Morsin, Marlia; Nayan, Nafarizal; Jumadi, Nur Anida; Razali, Nur Liyana; Md Shah, Nur Zehan An Nisa (International Journal of Integrated Engineering, 2017)
Herein, we propose a seed-mediated growth method for synthesis of gold nanorices directly grown on the substrate using silver seed. The as prepared sample was characterized using UV-Vis spectrometer, field emission scanning electron microscopy (FESEM), and X-Ray diffraction (XRD). The UV-Vis spectrum of the sample shows transversal surface plasmon resonance (t-SPR) peak at wavelength 541 nm and longitudinal surface plasmon resonance (l-SPR) peak at wavelength 730 nm. The FESEM image confirmed the morphology of gold nanostructures are rice-like shape. Typically, the nanorices have long axis (a) 55.54±3.30 nm, short axis (b) 28.71±2.30 nm, and aspect ratio (a/b) 1.98±0.09. The XRD pattern of the sample at diffraction angle (2θ) in the range of 10º-70º reveals three peaks at 38.18º, 44.48º, and 64.67º which corresponding to (111), (200), and (220) Bragg’s reflection of face centers cubic lattice Gold (ICSD file No. 98-005-3763). The strong peak intensity at 38.18º represents the nanorices growth in the (111) direction. The gold nanostructures with rice-like shape which exhibit two localized surface plasmon resonance (LSPR) thus it has very potential for application in plasmonic sensing